Assessing the Principal Agent Problem in Mobile Money Services: Lessons from M – PESA in Lesotho - Thabane, Matela (Research of GSB, 2019)
The expansion and diffusion of mobile phones globally has resulted in the provision of financial transactional services over the existing mobile phone platforms, generally referred to as mobile money. The supply end of mobile money services is an important factor in the success of the financial transactions offering. This research assessed vulnerabilities in the mobile money supply network that are inherently related to the existence of the principal – agent problem and their implications on availability and access to the services. The research study was conducted using a qualitative approach. Qualitative information was collected through interviews guided by open – ended questionnaires. Thematic analysis approach was followed to systematically analyse the data and generate findings of the study. Agent transactional data was analysed to complement the findings from qualitative analysis The findings suggest that the principal agent problem permeates the mobile money delivery network mainly after businesses joining as agents and manifests as moral hazard. Moral hazard is the dominant feature of the principal – agent problem, with adverse selection very low. Drivers of moral hazard are demonstrated by the influences and demands of agents’ core businesses and challenges in agent monitoring and training. The existence of the principal – agent problem has limited or no implications on access and availability of services. However, overtime the combined vulnerabilities identified related to the principal agent problem are likely to manifest into risks that are likely to affect access and availability of mobile money services. Regulators, Mobile Network Operators and agent enterprises must collectively review monitoring approaches for mobile money service providers to address challenges identified and increase the effectiveness of monitoring. Service provision standards should be reviewed to suit the various business environments the services are provided within. Mobile Network Operators and agent enterprises need to institute stronger partnership arrangements that enhance ownership and obligations for all parties, in particular agent enterprises. Agreements must enable application of different mobile money delivery models suitable to meet the demands and requirements of the agents’ core businesses. Innovations such as Near Field Communication (NFC) can be integrated with Point of sale (POS) applications and mobile money platforms to reduce the administration burden on agents and human error. Such applications must consider the cost implications of adoption from the agents’ business perspective.